Pengaruh Citra Merek dan Pandangan Kualitas Terhadap Kepercayaan Konsumen Pada McDonald’s Bandung - Yolanda, Elsa; Alamsyah, Doni Purnama (LPPM Universitas BSI, 2013)
ABSTRACT - Build consumer trust in the company is very important, variable brand image and pe rceived quality of the view one of the variables in Indonesia owned franchises such as McDonald's. The purpose of this study was to determine the influence of brand image and perceived quality for consumer trust. Sampleof 100 respondentswereused, namelyconsumerswhopurchaseproductsMcDonald's. The method of research used descriptive and regression analysis includes quantitative validity and reliability, the classic assumption test, multiple regression analysis, determination test, correlation coefficient test, F test. The results prove that the two independent variables brand image, and perceived quality has a positive and significant effect on the dependent variable is consumer trust in McDonald's. Greatest positive effect on consumer confidence is the variable perceived quality. Keywords: brand image, perceived quality